EFFECT OF HYDROTHERMAL DEWATERING ON COKE ADDITIVE MAKING FROM LOW RANK COAL (LRC) - Nining Sudini Ningrum; Miftahul Huda; Suganal Suganal (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2013)
This paper describes a study of the effects of hydrothermal dewatering (HTD) of Jambi, Pendopo and Wahau low rank coals, on additive characteristics. Hydrothermal upgrading and dewatering of the coals were carried out in a batch-type autoclave reactor at temperatures 350°C at a maximum pressure of 30 bar for 30 min. The dried sample resulted from hydrothermal process mixed with liquid fraction tar solvent at 250-350°C with ratio 4:6, was input in the 0,5 l autoclave to conduct hydrogenation process with variation initial hydrogen pressure of 10, 20, 30, 40, 50 bar, and reaction temperature of 400°C for 1 hour. The process of hydrothermal treatment before hydrogenation produced a higher calorific value having an average of >8000 cal/g (air dried basic, adb). Ash content and volatile matter for the coal were increased with the increasing initial hydrogen pressure. Corrected hydrogen content steadily increased after hydrothermal process and hydrogenation while the corrected oxygen decreased drastically after the hydrogenation process. Fuel ratio of Jambi, Pendopo and Wahau coals after hydrothermal process also increase reached 1.58, 1.04 and 1.77 respectively. Overall results indicate the impor- tance of introducing a hydrothermal treatment step for the improvement of the coke additive characteristics.